2020
DOI: 10.3390/cells9092098
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Comparison of Hyperglycemia-Induced Extracellular Vesicle Transcriptome in Different Mouse Stem Cells

Abstract: Extracellular vesicles (EVs) derived from stem /progenitor cells harbor immense potential to promote cardiomyocyte survival and neovascularization, and to mitigate ischemic injury. However, EVs’ parental stem/progenitor cells showed modest benefits in clinical trials, suggesting autologous stem cell/EV quality might have been altered by stimuli associated with the co-morbidities such as hyperglycemia associated with diabetes. Hyperglycemia is a characteristic of diabetes and a major driving factor in cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Previously, we have reported that EPCs and other stem cells exposed to hyperglycemic culture conditions showed a dramatic alteration in EV RNA contents 14 . In this study, we performed comprehensive studies demonstrating that diabetes impairs EPC-EV functions both in vitro cell culture system and in vivo in two models of myocardial injury.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, we have reported that EPCs and other stem cells exposed to hyperglycemic culture conditions showed a dramatic alteration in EV RNA contents 14 . In this study, we performed comprehensive studies demonstrating that diabetes impairs EPC-EV functions both in vitro cell culture system and in vivo in two models of myocardial injury.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is also being recognized that EV production, their cargo constituents and their functional activity depend largely on the pathophysiological environment of their parental cells 12 . Our previous studies have shown that external stimuli/stress such as inflammation and hyperglycemia changes EPC/stem cell-derived EV contents and functional properties 13 , 14 . In addition, EVs from diabetic plasma have been shown to be deficient in protecting cardiomyocytes 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Although diabetes does not affect the size and concentration of exosomes, they have a significant effect in altering the exosomes cargoes, thereby affecting the functional ability of exosomes [ 31 , 99 , 110 , 111 ]. Kim et al attributed dysregulated glucose metabolism to the altered circulating exosomal miRNA profile in obese diabetic individuals in comparison to healthy controls [ 112 ].…”
Section: Exosomes In Dhd and Their Therapeutic Potentialmentioning
confidence: 99%
“…Transcriptomic analysis of EVs derived from endothelial progenitor cells (EPCs), cardiac progenitor cells (CPCs), and cortical bone stem cells revealed the differential and similar composition of various mRNAs, miRNAs, and other noncoding RNAs [ 32 ]. Interestingly, this composition differed when parent cells were exposed to hyperglycemic conditions, implying selective genetic compositions based on the microenvironment or disease condition [ 32 ]. A class of long noncoding RNAs resulting from back splicing in the lariat splicing event process entrapped in exosomes could play a prominent role in CVD remodeling [ 22 ].…”
Section: Biology Of Exosomesmentioning
confidence: 99%